GROWTH OF THE ECONOMY'S AGRICULTURAL SECTOR BASED ON PROMOTING ENTREPRENEURSHIP (American Journal of Business Management, Economics and Banking, 2025)
The growth of the agricultural sector is crucial for the overall economic development of any nation. One of the most effective ways to foster this growth is by promoting entrepreneurship within the sector. Entrepreneurial activities in agriculture, such as establishing agri-businesses, utilizing innovative farming techniques, and integrating sustainable practices, are essential for increasing productivity, creating jobs, and improving food security. This paper explores the role of entrepreneurship in driving the economic growth of the agricultural sector, analyzing key strategies and innovations that can stimulate growth and enhance the sector’s competitiveness. The promotion of entrepreneurship in agriculture not only boosts local economies but also contributes to rural development and poverty alleviation.